2016
DOI: 10.1210/jc.2016-1624
|View full text |Cite
|
Sign up to set email alerts
|

FKBP5 mRNA Expression Is a Biomarker for GR Antagonism

Abstract: The inhibition of FKBP5 mRNA expression by a selective GR antagonist is a potential clinical biomarker of GR antagonism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 19 publications
4
28
0
Order By: Relevance
“…10 had also indicated that expression of GILZ, a key GR-responsive endogenous regulator of immune responses, and FKBP5, a key regulator of steroid hormone receptors as part of the heat shock protein 90 steroid receptor complex mRNA, had potential roles as biomarkers specifically linked to GR activation. 12 In the present study prednisone was clearly demonstrated to have the expected effects on all the biomarkers examined. Mifepristone was used as an active control in the single-dose study.…”
Section: Pharmacodynamicssupporting
confidence: 61%
See 3 more Smart Citations
“…10 had also indicated that expression of GILZ, a key GR-responsive endogenous regulator of immune responses, and FKBP5, a key regulator of steroid hormone receptors as part of the heat shock protein 90 steroid receptor complex mRNA, had potential roles as biomarkers specifically linked to GR activation. 12 In the present study prednisone was clearly demonstrated to have the expected effects on all the biomarkers examined. Mifepristone was used as an active control in the single-dose study.…”
Section: Pharmacodynamicssupporting
confidence: 61%
“…Compared with the effect of prednisone alone, coadministration with a single 600‐mg dose of mifepristone decreased FKBP5 expression approximately 10‐fold and GILZ expression approximately 3‐fold, which were to near preprednisone dose levels. Coadministration of CORT125134 (500 mg as a single dose or 250 mg daily for 14 days) with prednisone showed effects similar to those observed with mifepristone in combination with prednisone …”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…GCs cause the mobilization of energetic substrates from peripheral sources such as the liver, skeletal muscle, and adipose tissue [ 10 ]. Among the genes regulated by GCs, FK506-binding protein 51 (FKBP51) has been described as an important marker for GR sensitivity and bioavailability [ 11 , 12 ]. FKBP51 is a co-chaperone that modulates GC responses by negatively regulating GR activity, with their role in inflammation, autophagy, and insulin resistance having recently been discovered [ 13 ].…”
Section: Introductionmentioning
confidence: 99%